Poizvedovanje po slikah na podlagi vsebine - Kranjc, Tomaž (Knjižnica, 2007)
With development of technology, large image databases have become reality. Pictures in these databases were mainly described with keywords, but due to insufficiency of such description, the need for different approach to image indexing and retrieval has arisen. Content-based image retrieval is an alternative to textual based systems. Images are indexed on the basis of their actual content, features like color, texture and shape are presented numerically. In retrieval process, features for input image are extracted with the same algorithm as used for pictures already stored in the database, and values are compared. Such systems are known as CBIR (content-based image retrieval) systems. Basic characteristics of CBIR systems, which are freely available on the Internet, are presented. The systems are compared with respect to the environment in which they were built, applied features for content description and ability of user interface.
Keywords: informacijska tehnologija; information technology; informacijski sistemi; Internet; sistemi za poizvedovanje; CBIR sistemi; slike; slikovno gradivo; vizualne informacije; indeksiranje